2019
DOI: 10.1021/acs.nanolett.8b04309
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Bexarotene Aerosol Formulation Inhibits Major Subtypes of Lung Cancer in Mice

Abstract: Bexarotene has shown inhibition of lung and mammary gland tumorigenesis in preclinical models and in clinical trials. The main side effects of orally administered bexarotene are hypertriglyceridemia and hypercholesterolemia. We previously demonstrated that aerosolized bexarotene administered by nasal inhalation has potent chemopreventive activity in a lung adenoma preclinical model without causing hypertriglyceridemia. To facilitate its future clinical translation, we modified the formula of the aerosolized be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Importantly, with the combination of high anti-tumor efficacy and a favorable safety profile, rexinoids may be utilized in either clinical setting 27 . While recent strategies utilizing novel aerosolized delivery systems for administration of bexarotene have been effective in rodent models of lung cancer without inducing hypertriglyceridemia or hypercholesterolemia 43 , 44 , it is prudent to continue to synthesize new RXR agonists with improved efficacy and toxicity profiles in addition to optimizing drug delivery strategies. A combination of these two strategies may yield the best results.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, with the combination of high anti-tumor efficacy and a favorable safety profile, rexinoids may be utilized in either clinical setting 27 . While recent strategies utilizing novel aerosolized delivery systems for administration of bexarotene have been effective in rodent models of lung cancer without inducing hypertriglyceridemia or hypercholesterolemia 43 , 44 , it is prudent to continue to synthesize new RXR agonists with improved efficacy and toxicity profiles in addition to optimizing drug delivery strategies. A combination of these two strategies may yield the best results.…”
Section: Discussionmentioning
confidence: 99%
“…Bexarotene is a synthetic high-affinity retinoid X receptor agonist that is currently used clinically for the treatment of T-cell lymphoma (Talpur et al, 2002). In preclinical mouse models, bexarotene has also been confirmed to inhibit the occurrence of lung tumors (Zhang et al, 2019). Some studies have demonstrated that bexarotene exerts anti-inflammatory effects by downregulating the expression of interleukin (IL)-6, IL-8, monocyte chemoattractant protein 1 (MCP-1) and high mobility group box-1 (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Reproduced with permission. [ 10 ] Copyright 2019, American Chemical Society. The proportion of driver mutation of SCC and ADC was previously published.…”
Section: Nanotechnology In the Treatment Of Lung Cancermentioning
confidence: 99%